2011
DOI: 10.1007/s00431-011-1463-0
|View full text |Cite
|
Sign up to set email alerts
|

Infantile cortical hyperostosis and COL1A1 mutation in four generations

Abstract: Infantile cortical hyperostosis (ICH, OMIM 114000) is a rare familial disorder which affects infants. It spontaneously heals in the first years of life. The disease is characterized by regressive subperiosteal hyperosteogenesis mainly affecting long bones, mandible, clavicles, and ribs which are remarkably swollen and deformed on X-rays. But it is also important to take into consideration the autosomal dominant pattern of inheritance to detect it. In 2005 Gensure et al. detected 3040C→T mutation in COL1A1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Although some authors refer that the bone changes persist into adolescence and adulthood, others as Gensure et al report that studied patients with COL1A1 mutations had no skeletal deformity after childhood. In the study of four generations of a family affected with Caffey disease (Cerruti-Mainardi et al 13), COL1A1 mutation was identified in nine members of this family, reaching all target height and showing no bone changes sequelae in adulthood.
Learning points

Caffey disease or infantile cortical hyperostosis is an inflammatory proliferative bone disease, which has an onset within the first 6 months of life and usually resolves without sequelae by 2 years.

It is characterised by a triad of systemic symptoms (irritability and/or fever), soft-tissue swelling and underlying cortical bone thickening; most often involving the mandible (95% of cases), as well as ribs, shoulder blades and long bones (affect only the diaphyses, sparing the epiphyses and metaphyses).

In most cases, a good clinical history, basic laboratory evaluation and plain radiographs demonstrating periosteal involvement are sufficient to confirm this diagnosis.

Caffey disease, although rare, should not be forgotten in the diagnostic approach to early childhood bone swellings.

A high index of suspicion is necessary to establish this diagnosis, avoiding protracted investigations and unnecessary treatment for this otherwise self-limiting illness.

…”
Section: Discussionmentioning
confidence: 91%
“…Although some authors refer that the bone changes persist into adolescence and adulthood, others as Gensure et al report that studied patients with COL1A1 mutations had no skeletal deformity after childhood. In the study of four generations of a family affected with Caffey disease (Cerruti-Mainardi et al 13), COL1A1 mutation was identified in nine members of this family, reaching all target height and showing no bone changes sequelae in adulthood.
Learning points

Caffey disease or infantile cortical hyperostosis is an inflammatory proliferative bone disease, which has an onset within the first 6 months of life and usually resolves without sequelae by 2 years.

It is characterised by a triad of systemic symptoms (irritability and/or fever), soft-tissue swelling and underlying cortical bone thickening; most often involving the mandible (95% of cases), as well as ribs, shoulder blades and long bones (affect only the diaphyses, sparing the epiphyses and metaphyses).

In most cases, a good clinical history, basic laboratory evaluation and plain radiographs demonstrating periosteal involvement are sufficient to confirm this diagnosis.

Caffey disease, although rare, should not be forgotten in the diagnostic approach to early childhood bone swellings.

A high index of suspicion is necessary to establish this diagnosis, avoiding protracted investigations and unnecessary treatment for this otherwise self-limiting illness.

…”
Section: Discussionmentioning
confidence: 91%
“…This has also been shown in large kindreds with vertical transmission of Caffey-Silverman disease. [12][13][14][15] The heterozygous COL1A1 mutation in the clinically unaffected mother of our patients suggests that reduced penetrance and not autosomal recessive inheritance explains the recurrence of the disorder in affected siblings of seemingly unaffected parents. Adequate genetic counselling requires molecular analysis of both parents of an affected child.…”
Section: Discussionmentioning
confidence: 69%
“…In 1930 Roske first reported a radiographic presentation of cortical hyperostosis, not associated to infectious or nutritional diseases and its characterization dates back to 1939 . Caffey and Silverman suggested a new syndrome, the so called of infantile cortical hyperostosis, that included unusual child irritability, soft tissue swelling, and cortical hyperostosis in multiples bones.…”
Section: Introductionmentioning
confidence: 99%
“…The antenatal onset is also related . Mandible is commonly involved site beyond the long bones, clavicles and ribs, with no predilection by ethnic origin or gender . Some authors describe cases affecting the mandible angle, bilaterally .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation